Sourcing of obsidian artifacts from Masis Blur, Armenia - Martirosyan-Olshansky, Kristine (ARAMAZD: Armenian Journal of Near Eastern Studies, 2018)
Situated on the left bank of the presently dry Hrazdan River in central Armenia, Masis Blur currently is one of the earliest recorded sedentary settlements in the Southern Caucasus. Excavations have revealed a deeply stratified settlement spanning the late 7th to the mid-5th millennium cal. BC and six major cultural horizons have been identified thus far. The cultural-chronological attribution of materials finds close parallels with the Late Neolithic materials found at the settlements of Aratashen and Aknashen-Khatunarkh in the Ararat plain and a more general similarity to materials found in Late Neolithic settlements in Georgia and Azerbaijan. The currently available radiometric data place the occupation at Masis Blur slightly before the other known Neolithic sites in the region; however, a more robust set of radiocarbon dates is needed to assess these findings with more certainty.